Process for preparation of c2-C4 hydrocarbons and self-binding mixed catalysts
By preparing a self-adhesive mixed catalyst and using an activated zirconia binder, the problems of low carbon conversion and poor long-term stability in the synthesis method of existing catalysts are solved, and efficient conversion and high yield of C2 to C4 hydrocarbons are achieved.
Patent Information
- Application Number
- CN202380053937.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-04
AI Technical Summary
In the synthesis method, existing catalysts have problems of low carbon conversion and poor long-term stability, resulting in a decrease in hydrocarbon yield.
A self-bonding mixing catalyst is used, which utilizes an active zirconium oxide binder to prevent dopant migration and improve the long-term stability of the catalyst by adding the impregnation solution to the mixed base catalyst support.
High conversion and high yields of C2 to C4 hydrocarbons are achieved, which improves the long-term stability and activity of the catalyst and avoids dilution and structural damage caused by inactive binders.
Smart Images

Figure BDA0005242879730000161
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 63 / 391,487, filed on July 22, 2022, which is hereby incorporated by reference in its entirety. Technical Field
[0003] The present disclosure relates to the preparation of self-binding hybrid catalysts and the use of the self-binding hybrid catalysts to achieve high conversion of synthesis gas feeds, resulting in good carbon conversion and high yields of desired products. Background Art
[0004] For many industrial applications, hydrocarbons are used or used as starting materials to produce plastics, fuels and various downstream chemicals. Such hydrocarbons include C2 to C4 materials such as ethene, propene and butene (also commonly referred to as ethylene, propylene and butylene, respectively). A variety of processes have been developed for the production of these lower hydrocarbons, including petroleum cracking and various synthetic methods.
[0005] Synthetic processes for converting feed carbon into desired products, such as hydrocarbons, are known. Different types of catalysts and different types of feed streams and ratios of feed stream components have been developed. Since the catalysts usually need to be loaded into commercial reactors in a shaped form, such catalysts usually include an inert and / or non-active binder to provide structural stability.
[0006] Therefore, when used in these synthesis processes, the resulting mixed catalysts containing inert binders often suffer from low carbon conversion because they dilute the concentration of active components, where much of the feed carbon (1) is not converted and leaves the process in the same form as the feed carbon; (2) is converted to CO2; or (3) these synthesis processes become less stable over time and the catalyst quickly loses its activity in converting carbon to the desired product. For example, many synthesis processes tend to have a reduced CO2 over time. x The conversion rate is increased, thereby having a reduced production of C2 to C4 hydrocarbons. Therefore, a catalyst having high operating stability and a method for preparing the catalyst are needed. Summary of the invention
[0007] It has been found that many conventional catalysts employ inactive binders which promote migration of dopants from the mixed metal oxide catalyst component of the hybrid catalyst to the binder, which can compromise the long term stability of these catalysts. In addition, inactive binders dilute the active components in the reactor volume.
[0008] Embodiments of the present disclosure solve these needs and other needs by preparing a self-bonding mixed catalyst and a method using such a catalyst. The method for preparing a self-bonding mixed catalyst includes adding an impregnation solution to a mixed base catalyst carrier. The mixed base catalyst carrier comprises a metal oxide catalyst carrier, a microporous catalyst component and a binder, wherein the metal oxide catalyst carrier and the microporous catalyst component are combined into a single catalyst body using a binder. The binder in the mixed base catalyst carrier is substantially composed of the same material as the metal oxide catalyst carrier. The impregnation solution includes a solution containing one or more dopants, which is introduced into the mixed base catalyst carrier by one or more dopants to form a self-bonding mixed catalyst. This self-bonding mixed catalyst can then be used to directly convert a feed stream (such as synthesis gas) containing hydrogen and carbonaceous gas into C2 to C4 hydrocarbons. The metal oxide catalyst carrier and the microporous catalyst component can be operated in series so that the self-bonding mixed catalyst can directly and selectively convert a feed stream (such as synthesis gas) containing hydrogen and carbonaceous gas into C2 to C4 hydrocarbons with a high olefin / paraffin ratio.
[0009] According to one or more embodiments of the present disclosure, a method for preparing a self-binding hybrid catalyst may include mixing a powder mixture and a binder component to form a hybrid base catalyst; and adding an impregnation solution comprising gallium to the hybrid base catalyst to form a self-binding hybrid catalyst after drying and calcining. The powder mixture may include a metal oxide catalyst support and an 8-membered ring (8-MR) microporous catalyst component, wherein the metal oxide catalyst support may include zirconium oxide. The binder component may include a zirconium salt solution, a zirconium salt gel, a zirconium salt slurry, a slurry of a carbonate or oxide or hydroxide of zirconium, or a colloidal solution of a carbonate or oxide or hydroxide of zirconium, wherein the binder component may have a pH of 2 to 8.
[0010] According to one or more embodiments of the present disclosure, a method for preparing C2 to C4 hydrocarbons may include introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a self-binding mixed catalyst formed according to the method of the present disclosure.
[0011] Additional features and advantages will be set forth in the following Detailed Description, and in part will become apparent to those skilled in the art from that description or may be learned by practicing the embodiments described herein, including the following Detailed Description and claims.
[0012] It is to be understood that both the foregoing general description and the following detailed description describe various embodiments, and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. DETAILED DESCRIPTION
[0013] Reference will now be made specifically to embodiments of methods for preparing C2 to C4 hydrocarbons and preparing self-bonding hybrid catalysts. In one or more embodiments, the method for preparing a self-bonding hybrid catalyst may include mixing a powder mixture and a binder component to form a mixed base catalyst support, and adding an impregnation solution to the mixed base catalyst support to form a self-bonding hybrid catalyst. The powder mixture may include a metal oxide catalyst support and a microporous catalyst component. The metal oxide catalyst support may include zirconium oxide. The binder component may include one or more zirconium salt solutions, zirconium salt gels, zirconium salt slurries, slurries of zirconium carbonate, zirconium oxide or zirconium hydroxide, or colloidal solutions of zirconium carbonate, zirconium oxide or zirconium hydroxide. The binder component may have a pH of 2 to 8.
[0014] In one or more embodiments, a method for preparing C2 to C4 hydrocarbons may include introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a self-binding mixed catalyst. The self-binding mixed catalyst can be formed by the method for preparing the self-binding mixed catalyst described herein.
[0015] The use of this mixed catalyst is known in the field of hydrocarbon products such as diesel or aromatic compounds. However, many known mixed catalysts are inefficient for forming C2 to C4 hydrocarbons, C2 to C4 paraffins and C2 to C4 olefins by the feed stream comprising hydrogen and carbonaceous gas, because they show low feed carbon conversion, and / or deactivate quickly during use. In addition, many known mixed catalysts adopt the inactive binder that usually comprises aluminum oxide, which can promote dopant to migrate to binder from the metal oxide catalyst support of mixed catalyst, and can damage the long-term stability of catalyst. In addition, without being bound by any particular theory, it is believed that the inactive binder of mixed catalyst can reduce the amount of active material that can be used for forming C2 to C4 hydrocarbons by the feed stream comprising hydrogen and carbonaceous gas on the mixed catalyst, which may cause the performance of catalyst in operation to decrease due to the inactive binder occupying volume and diluting the active components in the fixed reactor volume.
[0016] In contrast, the self-bound hybrid catalyst disclosed and described herein utilizes an active zirconia binder and thus prevents the negative effects of any migration of one or more dopants from the metal oxide catalyst support to the inactive binder, thereby improving the long-term stability of the catalyst.
[0017] When compared with a mixed catalyst in which a metal oxide catalyst support and a microporous catalyst component are physically mixed (for example, a mixed catalyst without forming a single particle bonding together), the self-bonding mixed catalyst shows a high and stable yield of particularly C2 to C4 hydrocarbons, even if the catalyst operation time increases. Not bound by theory, and as a summary, the self-bonding mixed catalyst closely combines the independent reactions on each of the two independent catalysts. In the first step, the feed stream (such as synthesis gas) of the carbonaceous gas of the group composed of a mixture of hydrogen (H2) and selected from carbon monoxide (CO), carbon dioxide (CO2) or CO and CO2 can be mainly converted into intermediates, such as oxygenated hydrocarbons, by the metal oxide catalyst component. In subsequent steps, these intermediates can be converted into a product stream comprising hydrocarbons (mainly short-chain hydrocarbons, such as C2 to C4 hydrocarbons) mainly by the microporous catalyst component. The continuous formation and consumption of the intermediate oxygenated compound formed by the reaction of the second step in the first step ensure that there is no thermodynamic limitation to conversion. In one or more embodiments, the self-binding hybrid catalyst can be formed by mixing powders of the metal oxide catalyst support component and the microporous catalyst component with a binder solution, wherein the binder solution contains the same metal component as in the metal oxide catalyst support.
[0018] In one or more embodiments, the term "metal oxide catalyst support" may refer to a support material for a monolithic self-bound hybrid catalyst, wherein the support material comprises zirconium oxide (i.e., zirconium oxide (zirconia)). In one or more embodiments, the term "microporous catalyst component" may refer to a catalyst component comprising a catalyst having [SiO4] and [AlO4] - A molecular sieve zeolite component of a crystalline aluminosilicate having a three-dimensional interconnected network of tetrahedra. In one or more embodiments, the term "microporous catalyst component" may refer to a catalyst component having [PO4] + and [AlO4] - A molecular sieve zeolite component of a crystalline silicoaluminophosphate of a three-dimensional interconnected network of tetrahedra, wherein aluminum or phosphorus is partially substituted with silicon. In one or more embodiments, the term "hybrid base catalyst support" may refer to a composition in which a metal oxide catalyst support and a microporous catalyst component are bound together by a binder component, wherein the binder component may consist essentially of the same material or materials as the metal oxide catalyst support. In one or more embodiments, the term "self-bound hybrid catalyst" may refer to a catalyst in which a hybrid base catalyst support is impregnated with one or more dopants, which may include, but are not limited to, gallium and lanthanum.
[0019] In an embodiment, the metal oxide catalyst component is supported on zirconium oxide (ZrO2). In an embodiment, the zirconium oxide support of the metal oxide catalyst component can be phase-pure zirconium oxide. As used herein, "phase-pure zirconium oxide" refers to zirconium oxide without intentional addition of other materials during formation. Therefore, phase-pure zirconium oxide includes zirconium oxide with a small amount of components different from zirconium (including oxides different from zirconium oxide), which are unintentionally present in zirconium oxide as a natural part of the zirconium oxide formation process, such as hafnium (Hf). In other embodiments, zirconium oxide can be non-phase-pure zirconium oxide, such as zirconium oxide doped with calcium, yttrium oxide, lanthanum, cerium or rare earth elements. In an embodiment, zirconium oxide may include zirconium oxide particles having a crystalline structure. In an embodiment, zirconium oxide includes zirconium oxide particles having a monoclinic structure. In one or more embodiments, zirconium oxide is substantially composed of crystalline zirconium oxide particles or is composed of crystalline zirconium oxide particles. In an embodiment, zirconium oxide is substantially composed of monoclinic zirconium oxide particles or is composed of monoclinic zirconium oxide particles.
[0020] In an embodiment, the metal oxide catalyst component comprises gallium oxide. As used herein, "gallium oxide" refers to gallium in various oxidation states. In an embodiment, the gallium oxide may be deposited on the surface of zirconium oxide or form a solid solution with ZrO2. In other embodiments, the gallium oxide may include, but is not limited to, Ga2O3, GaO(OH), and Ga5O 7- (OH). Gallium oxide may also include polymorphs of Ga2O3, such as monoclinic (β-Ga2O3), rhombohedral (α-Ga2O3), defect spinel (γ-Ga2O3), cubic (δ-Ga2O3), or orthorhombic (ε-Ga2O3) structures. In other embodiments, gallium oxide may include gallium in more than one oxidation state. For example, individual galliums may be in different oxidation states. Gallium oxide is not limited to comprising gallium in a uniform oxidation state.
[0021] In one or more embodiments, the metal oxide catalyst support may be mixed with a microporous catalyst component. In an embodiment, the microporous catalyst component may be selected from a molecular sieve having an 8-membered ring (MR) pore opening and having a framework type selected from the group consisting of the following framework types: CHA, AEI, AFX, ERI, LEV, LTA, UFI, RTH, EDI, GIS, MER, RHO and combinations thereof, which framework types correspond to the naming conventions of the International Zeolite Association. It should be understood that in an embodiment, both aluminosilicates and silicoaluminophosphate frameworks may be used. The embodiment may include tetrahedral aluminosilicates, ALPO (e.g., tetrahedral aluminophosphates), SAPO (e.g., tetrahedral silicoaluminophosphates) and only silica-based framework silicates. In certain embodiments, the microporous catalyst component may be a silicoaluminophosphate having a chabazite (CHA) framework type. Examples of these may include, but are not necessarily limited to: CHA embodiments selected from SAPO-34 and SSZ-13; and AEI embodiments, such as SAPO-18 and SSZ-39. A combination of microporous catalyst components having any of the above framework types can also be used. It should be understood that, depending on the desired product, the microporous catalyst component can have different ring pore openings. For example, depending on the desired product, a microporous catalyst component with an 8-MR to 12-MR pore opening can be used. However, in order to produce C2 to C4 hydrocarbons, a microporous catalyst component with an 8-MR pore opening is used in an embodiment.
[0022] In one or more embodiments, a binder solution may be mixed with a powder mixture of a metal oxide catalyst support and a microporous catalyst component to form a mixed base catalyst support. The binder solution may include a zirconium salt solution, a zirconium salt gel, a zirconium salt slurry, a slurry of zirconium carbonate, zirconium oxide or zirconium hydroxide, or a colloidal solution of zirconium carbonate, zirconium oxide or zirconium hydroxide. In one embodiment, the binder solution may consist of zirconium acetate. In another embodiment, the binder solution may consist of zirconium oxynitrate. In another embodiment, the binder solution may consist of zirconium oxide or zirconium hydroxide. In an embodiment, the binder solution may include a mixture of one or more of zirconium acetate, zirconium oxynitrate, ammonium zirconium carbonate, zirconium hydroxide and zirconium oxide.
[0023] In one or more embodiments, the binder solution may have a pH of 2.0 to 8.0, such as 2.5 to 8.0, 3.0 to 8.0, 3.5 to 8.0, 4.0 to 8.0, 4.5 to 8.0, 5.0 to 8.0, 5.5 to 8.0, 2.0 to 5.5, 2.5 to 5.5, 3.0 to 5.5, 3.5 to 5.5, 4.0 to 5.5, 4.5 to 5.5, 5.0 to 5.5, 2.0 to 5.0, 2.5 3.5, 3.0 to 3.5, 2.0 to 2.5, 2.5 to 3.0, 3.5 to 3.5, 2.0 to 2.5, 3.0 to 3.5, 2.5 to 3.0, 3.5 to 3.5, 2.0 to 3.0, 2.5 to 3.0, or 2.0 to 2.5. For example, in embodiments, the pH of the binder solution can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, or 8. Without being bound by theory, it is believed that when the binder solution has a pH above 8, the binder solution becomes too basic and may damage the structural integrity of the microporous catalyst component when the binder solution is added to the powder mixture. In addition, without being bound by theory, it is believed that when the binder solution has a pH below 2, the binder solution becomes too acidic and may damage the structural integrity of the microporous catalyst component when the binder solution is added to the powder mixture.
[0024] Metal oxide catalyst support, microporous catalyst component and binder solution can be mixed together by any suitable means, to realize uniform mixing of all components before extrusion.Metal oxide catalyst support and microporous catalyst component can be mixed in powder form initially, to realize uniformity in suitable dry mixer, such as ribbon or plow mixer.Metal oxide catalyst support, microporous catalyst component and binder solution can be combined, produce the catalyst of mass ratio being 1:10 to 10:1, make the mass ratio of metal oxide catalyst support and binder component and microporous catalyst component be 1:1,1:2,1:3,1:4,1:5,1:6,1:7,1:8,1:9 or 1:10, and the mass ratio of microporous catalyst component and metal oxide catalyst support is 1:1,1:2,1:3,1:4,1:5,1:6,1:7,1:8,1:9 or 1:10.
[0025] After the powder mixture and the binder solution are mixed, a mixed base catalyst support can be formed. In an embodiment, the powder mixture and the binder solution are mixed to form an initial paste. The initial paste can be mixed until an extrudable paste is formed, and a mixed base catalyst support is formed using a method known to those skilled in the art. The mixed base catalyst support can then be dried at a temperature of at least 40°C. For example, the mixed base catalyst support can be dried at a temperature of 40°C to 200°C. In an embodiment, the mixed base catalyst support can be dried at a temperature of 60°C to 200°C, 80°C to 200°C, 100°C to 200°C, 120°C to 200°C, 140°C to 200°C, or 160°C to 200°C. In an embodiment, the mixed base catalyst support can be dried at a temperature of 40°C to 180°C, 40°C to 160°C, 40°C to 140°C, 40°C to 120°C, 40°C to 100°C, or 40°C to 80°C. In an embodiment, the mixed base catalyst support is further used in its dried form. In alternative embodiments, the dried hybrid base catalyst support may be calcined at a temperature of 200° C. to 800° C. to form a hybrid base catalyst support. In embodiments, the dried hybrid base catalyst support may be calcined at a temperature of 200° C. to 700° C., 200° C. to 600° C., 200° C. to 500° C., 200° C. to 400° C., or 200° C. to 300° C. In embodiments, the dried extrudable paste may be calcined at a temperature of 300° C. to 800° C., 400° C. to 800° C., 500° C. to 800° C., 600° C. to 800° C., or 700° C. to 800° C.
[0026] In embodiments, the hybrid base catalyst support may have a particle size of 0.5 mm to 6.0 mm. For example, the hybrid base catalyst support may have a particle size of at least 0.5 mm, at least 1.0 mm, at least 1.5 mm, at least 2.0 mm, at least 2.5 mm, at least 3.0 mm, at least 3.5 mm, at least 4.0 mm, at least 4.5 mm, at least 5.0 mm, at least 5.5 mm, or even 6.0 mm. In embodiments, the hybrid base catalyst support may have a particle size in the range of 0.5 mm to 5.5 mm, 0.5 mm to 5.0 mm, 0.5 mm to 4.5 mm, 0.5 mm to 4.0 mm, 0.5 mm to 3.5 mm, 0.5 mm to 3.0 mm, 0.5 mm to 2.5 mm, 0.5 mm to 2.0 mm, or 0.5 mm to 1.5 mm. In embodiments, the hybrid base catalyst carrier may have a particle size in the range of 1.0 mm to 6.0 mm, 1.5 mm to 6.0 mm, 2.0 mm to 6.0 mm, 2.5 mm to 6.0 mm, 3.0 mm to 6.0 mm, 3.5 mm to 6.0 mm, 4.0 mm to 6.0 mm, 4.5 mm to 6.0 mm, 5.0 mm to 6.0 mm, or 5.5 mm to 6.0 mm. The particle size may be substantially the shortest dimension of the catalyst particles. For example, when the hybrid base catalyst carrier has a hollow cylinder or annular shape, the particle size is the thickness of the hollow cylinder wall. When the hybrid base catalyst carrier has a spherical shape, the particle size is the diameter of the sphere. The particle size of the hybrid base catalyst carrier can be controlled by selecting the extrusion die diameter and measured by a dynamic image analysis method.
[0027] In one or more embodiments, the impregnation solution may be added to the mixed base catalyst support to form a self-bonding mixed catalyst. In one or more embodiments, the impregnation solution may include lanthanum. In one or more embodiments, the impregnation solution may include one or more rare earth elements. The rare earth elements may include scandium, yttrium, and elements with atomic numbers from 57 to 71, such as, but not limited to, samarium, gadolinium, dysprosium, cerium, and neodymium. In embodiments, the impregnation solution may include gallium (III) nitrate (i.e., Ga (NO3) 3). In embodiments, the impregnation solution may include lanthanum (III) nitrate (i.e., La (NO3) 3). In embodiments, the impregnation solution may include both gallium (III) nitrate and lanthanum (III) nitrate. In embodiments, gallium may be added via a gallium-containing precursor.
[0028] In one or more embodiments, the impregnation solution may include a transition metal element such as nickel (Ni), palladium (Pd) or platinum (Pt). In an embodiment, the impregnation solution includes an alkali and may have a pH less than or equal to 10.0. For example, the impregnation solution may have a pH of 2.0 to 10.0. In an embodiment, the impregnation solution may have a pH of 2.5 to 7.5, 3.0 to 7.5, 3.5 to 7.5, 4.0 to 7.5, or 4.5 to 7.5. In an embodiment, the impregnation solution may have a pH of 2.0 to 4.5, 2.0 to 4.0, 2.0 to 3.5, 2.0 to 3.0, or 2.0 to 2.5. In an embodiment, the impregnation solution may have a pH of 5.0 to 10.0, 5.5 to 10.0, 6.0 to 10.0, 6.5 to 10.0, 7.0 to 10.0, 7.5 to 10.0, or 8.0 to 10.0.
[0029] In embodiments, the impregnation solution may include one or more chelating agents or complexing agents to ensure solubility of the metal ions at the desired concentration and the desired pH. The term "chelating agent" or "complexing agent" refers to a chemical agent that can contribute to the stability of the metal ion solution by binding to the metal ions and forming a soluble complex. In some embodiments, the chelating agent and / or complexing agent may include a carboxylic acid, an amino acid, an amine, a diol, or a combination thereof. In some embodiments, the impregnation solution may include ammonia, ethanolamine, diethanolamine, triethanolamine, or a combination thereof instead of or in addition to the chelating agent and / or complexing agent.
[0030] After mixing the mixed base catalyst support and the impregnation solution, a self-binding hybrid catalyst can be formed. The self-binding hybrid catalyst can be dried at a temperature of at least 40°C. For example, the self-binding hybrid catalyst can be dried at a temperature of 40°C to 200°C. In an embodiment, the self-binding hybrid catalyst can be dried at a temperature of 60°C to 200°C, 80°C to 200°C, 100°C to 200°C, 120°C to 200°C, 140°C to 200°C, or 160°C to 200°C. In an embodiment, the self-binding hybrid catalyst can be dried at a temperature of 40°C to 180°C, 40°C to 160°C, 40°C to 140°C, 40°C to 120°C, 40°C to 100°C, or 40°C to 80°C. The dried self-binding hybrid catalyst can then be calcined at a temperature of 200°C to 800°C. In embodiments, the dried self-binding mixed catalyst may be calcined at a temperature of 200° C. to 700° C., 200° C. to 600° C., 200° C. to 500° C., 200° C. to 400° C., or 200° C. to 300° C. In embodiments, the dried self-binding mixed catalyst may be calcined at a temperature of 300° C. to 800° C., 400° C. to 800° C., 500° C. to 800° C., 600° C. to 800° C., or 700° C. to 800° C.
[0031] In embodiments, the self-binding hybrid catalyst may have a particle size of 0.5 mm to 6.0 mm. For example, the self-binding hybrid catalyst may have a particle size of at least 0.5 mm, at least 1.0 mm, at least 1.5 mm, at least 2.0 mm, at least 2.5 mm, at least 3.0 mm, at least 3.5 mm, at least 4.0 mm, at least 4.5 mm, at least 5.0 mm, at least 5.5 mm, or even 6.0 mm. In embodiments, the self-binding hybrid catalyst may have a particle size in the range of 0.5 mm to 5.5 mm, 0.5 mm to 5.0 mm, 0.5 mm to 4.5 mm, 0.5 mm to 4.0 mm, 0.5 mm to 3.5 mm, 0.5 mm to 3.0 mm, 0.5 mm to 2.5 mm, 0.5 mm to 2.0 mm, or 0.5 mm to 1.5 mm. In embodiments, the self-bonding mixed catalyst can have a particle size in the range of 1.0 mm to 6.0 mm, 1.5 mm to 6.0 mm, 2.0 mm to 6.0 mm, 2.5 mm to 6.0 mm, 3.0 mm to 6.0 mm, 3.5 mm to 6.0 mm, 4.0 mm to 6.0 mm, 4.5 mm to 6.0 mm, 5.0 mm to 6.0 mm, or 5.5 mm to 6.0 mm. The particle size can be substantially the shortest dimension of the catalyst particles. For example, when the self-bonding mixed catalyst has a hollow cylinder or annular shape, the particle size is the thickness of the hollow cylinder wall. When the self-bonding mixed catalyst has a spherical shape, the particle size is the diameter of the sphere. The particle size of the self-bonding mixed catalyst can be controlled by selecting the extrusion die diameter and measured by a dynamic image analysis method.
[0032] Without being bound by theory, it is believed that because the impregnation solution is added to the hybrid base catalyst support after the hybrid base catalyst support is formed, dried and / or calcined, this allows the contents of the impregnation solution to be added to the entire hybrid base catalyst support, including the zirconia-based binder of the hybrid base catalyst support. Therefore, in the case where the impregnation solution is added to the entire hybrid base catalyst support (including the active zirconia-based binder), the amount of active components on the self-bound hybrid catalyst is increased, resulting in an increased yield of C2 to C4 hydrocarbons from a feed stream comprising hydrogen and a carbon-containing gas.
[0033] The self-binding hybrid catalyst can be used in a process for converting carbon in a carbon-containing feed stream into C2 to C4 hydrocarbons. As used herein, "carbon-containing feed stream" may refer to a gas selected from carbon monoxide, carbon dioxide, and mixtures thereof. As used herein, "synthesis gas" may refer to a gas comprising hydrogen and a carbon-containing gas. Such a process will be described in more detail below.
[0034] According to an embodiment, a feed stream may be fed into the reaction zone, the feed stream comprising hydrogen (H2) and a carbon-containing gas selected from carbon monoxide (CO), carbon dioxide (CO2), and combinations thereof. In an embodiment, the H2 gas is present in the feed stream in an amount of 10 volume percent (vol.%) to 90 vol.%, based on the total volume of the H2 gas and the gas selected from CO, CO2, and combinations thereof. The feed stream may contact the self-binding mixed catalyst as disclosed and described herein while in the reaction zone.
[0035] Without being bound by theory, it is understood that the activity of the self-binding mixed catalyst will be higher for feed streams containing CO as the carbon-containing gas, and the activity of the self-binding mixed catalyst may be reduced when a larger portion of the carbon-containing gas in the feed stream is CO. However, this is not to say that the self-binding mixed catalyst disclosed and described herein cannot be used in processes where the feed stream includes CO as all or a majority of the carbon-containing gas.
[0036] When in the reaction zone, the feed stream may be contacted with the self-binding mixed catalyst under reaction conditions sufficient to form a product stream comprising C2 to C4 hydrocarbons. According to one or more embodiments, the reaction conditions may include a temperature in the reaction zone in the range of 350°C to 480°C, such that the temperature is at least 350°C, at least 370°C, at least 390°C, at least 410°C, at least 430°C, or at least 450°C. In embodiments, the temperature in the reaction zone may be 370°C to 460°C, 390°C to 460°C, or 390°C to 450°C. In embodiments, the temperature in the reaction zone may be 370°C to 480°C, 390°C to 480°C, 410°C to 480°C, or 430°C to 480°C. In embodiments, the temperature in the reaction zone may be 350°C to 460°C, 350°C to 440°C, 350°C to 420°C, 350°C to 400°C, or 350°C to 380°C.
[0037] In embodiments, the reaction conditions include a pressure within the reaction zone of at least 1 bar (100 kilopascals (kPa), such as at least 5 bar (500 kPa), at least 10 bar (1,000 kPa), at least 15 bar (1,500 kPa), at least 20 bar (2,000 kPa), at least 25 bar (2,500 kPa), at least 30 bar (3,000 kPa), at least 35 bar (3,500 kPa), at least 40 bar (4,000 kPa), at least 45 bar (4,500 kPa), at least 50 bar (500 kPa), at least 55 bar (600 kPa), at least 50 bar (700 kPa), at least 50 bar (800 kPa), at least 55 bar (900 kPa), at least 50 bar (1000 kPa), at least 50 bar (1100 kPa), at least 50 bar (1200 kPa), at least 50 bar (1300 kPa), at least 50 bar (1500 kPa), at least 50 bar (1600 kPa), at least 50 bar (1700 kPa), at least 50 bar (1800 kPa), at least 50 bar (1900 kPa), at least 50 bar (1900 kPa), at least 50 bar (1 kPa), at least 50 bar (5,000 kPa), at least 55 bar (5,500 kPa), at least 60 bar (6,000 kPa), at least 65 bar (6,500 kPa), at least 70 bar (7,000 kPa), at least 75 bar (7,500 kPa), at least 80 bar (8,000 kPa), at least 85 bar (8,500 kPa), at least 90 bar (9,000 kPa), at least 95 bar (9,500 kPa), or at least 100 bar (10,000 kPa). kPa). In other embodiments, the reaction conditions include a pressure within the reaction zone of 5 bar (500 kPa) to 100 bar (10,000 kPa), such as 10 bar (1,000 kPa) to 95 bar (9,500 kPa), 15 bar (1,500 kPa) to 90 bar (9,000 kPa), 20 bar (2,000 kPa) to 85 bar (8,500 kPa), 25 bar (2,500 kPa) to 80 bar (8,000 kPa), 30 bar (3 ... In some embodiments, the pressure inside the reaction zone is from 20 bar (2,000 kPa) to 60 bar (6,000 kPa).
[0038] According to embodiments, the gas hourly space velocity (GHSV) in the reaction zone is from 500 per hour ( / hr) to 12,000 / hr, such as from 500 / hr to 10,000 / hr, from 1,200 / hr to 12,000 / hr, from 1,500 / hr to 10,000 / hr, from 2,000 / hr to 9,500 / hr, from 2,500 / hr to 9,000 / hr, from 3,000 / hr to 8,500 / hr, from 3,500 / hr to 8,000 / hr, from 4,000 / hr to 7,500 / hr, from 4,500 / hr to 7,000 / hr, from 5,000 / hr to 6,500 / hr, or from 5,500 / hr to 6,000 / hr. In embodiments, the GHSV within the reaction zone is from 1,800 / hour to 3,600 / hour, such as from 2,000 / hour to 3,600 / hour, 2,200 / hour to 3,600 / hour, 2,400 / hour to 3,600 / hour, 2,600 / hour to 3,600 / hour, 2,800 / hour to 3,600 / hour, 3,000 / hour to 3,600 / hour, 3,200 / hour to 3,600 / hour, or 3,400 / hour to 3,600 / hour. In embodiments, the GHSV within the reaction zone is from 1,800 / hour to 3,400 / hour, such as from 1,800 / hour to 3,200 / hour, from 1,800 / hour to 3,000 / hour, from 1,800 / hour to 2,800 / hour, from 1,800 / hour to 2,600 / hour, from 1,800 / hour to 2,400 / hour, from 1,800 / hour to 2,200 / hour, or from 1,800 / hour to 2,000 / hour. In embodiments, the GHSV within the reaction is from 2,000 / hour to 3,400 / hour, such as from 2,200 / hour to 3,200 / hour, from 2,400 / hour to 3,000 / hour, or from 2,600 / hour to 2,800 / hour.
[0039] In embodiments, when using the self-binding hybrid catalyst disclosed and described herein and the process conditions disclosed and described herein, carbon conversion can be increased. Within the disclosed process, the conversion of a feed containing carbon oxides and hydrogen can be carried out in a series of reactors with intermediate knock-out of water byproducts by means of, for example, phase separation, membrane separation, or some type of water selective absorption or adsorption process. Without being bound by theory, further continuously directing the partially converted and anhydrous effluent to subsequent reactors and repeating this technical mode of operation will have the overall effect of increasing hydrocarbon yields.
[0040] Example
[0041] The following examples illustrate features of the present disclosure, but are not intended to limit the scope of the present disclosure. For each of the following examples and comparative examples, a microporous catalyst component was prepared as follows: SAPO-34 was synthesized according to a literature procedure (Lok, BM; Messina, CA; Patton, RL; Gajek, RT; Cannan, TR; Flanigen, EM Crystalline silicoaluminophosphates. U.S. Pat. No. 4,440,871A, 1984). When calcined SAPO-34 was used, the material was calcined in air using the following procedure: from 25°C to 600°C at a heating rate of 2°C / min, maintained at 600°C for 4 hours (h), and cooled to 25°C within 4h. The material was sieved into a fraction of less than 200 mesh (less than 75 μm).
[0042] Example 1
[0043] The mixed base catalyst support was prepared by mixing 4 grams of a zirconium oxide component (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name RC-100) with 1 gram of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 2 minutes. Separately, 15 mL of a 20 wt % zirconium acetate solution (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Zircosol AC-20) was partially neutralized by slowly adding a 20 wt % zirconium carbonate ammonium (AZC) solution (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Zircosol ZA-20) at about 50° C. with stirring until a pH of 5 to 6 was obtained (a total of 1.8 mL of AZC solution was added). The Zr-containing binder solution was added to the dried mixed powder, aiming for a final ZrO2 binder concentration of 20 wt % based on total solids. The paste was then mixed using a mortar and pestle for at least 15 minutes until an extrudable paste was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated in a static muffle furnace at 2°C / min to a temperature of 250°C and kept at this temperature for 4 hours.
[0044] After calcination, the mixed base catalyst support was crushed and sieved into 40 mesh to 80 mesh.
[0045] Prepare stock solutions for impregnation. Add La(NO3)3×6H2O (0.9752 g) and Ga(NO3)3 2.04M stock solution (3.6805 mL) to a beaker and stir. Add citric acid (1.875 g) and stir until dissolved. Slowly neutralize the solution with concentrated ammonia until pH reaches 5. Add water to a total volume of 10 mL and homogenize.
[0046] The 40 to 80 mesh fractions were impregnated with Ga and La dopants by slowly adding the stock solution to the reticulated base catalyst in the vortex mixer solution (about 0.44 mL per gram of base catalyst support). The impregnated reticulated fraction was dried at 85°C overnight. The dried self-bound hybrid catalyst was then heated to 600°C at 2°C / min in a static muffle furnace and maintained at this temperature for 4 hours. After calcination, the self-bound hybrid catalyst was sieved into 40 to 80 mesh for testing.
[0047] Example 2
[0048] The mixed base catalyst support was prepared by mixing 4 grams of a zirconium oxide component (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Z3186) with 1 gram of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 2 minutes. Separately, 15 mL of a 20 wt % zirconium acetate solution (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Zircosol AC-20) was partially neutralized by slowly adding a 20 wt % zirconium carbonate ammonium (AZC) solution (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Zircosol ZA-20) at about 50° C. with stirring until a pH of 5 to 6 was obtained (a total of 1.8 mL of AZC solution was added). The Zr-containing binder solution was added to the dried mixed powder, aiming for a final ZrO2 binder concentration of 20 wt % based on total solids. The paste was then mixed using a mortar and pestle for at least 15 minutes until an extrudable paste was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated in a static muffle furnace at 2°C / min to a temperature of 250°C and kept at this temperature for 4 hours.
[0049] After calcination, the mixed base catalyst support was crushed and sieved into 40 mesh to 80 mesh.
[0050] Prepare stock solutions for impregnation. Add La(NO3)3×6H2O (0.9752 g) and Ga(NO3)3 2.04M stock solution (3.6805 mL) to a beaker and stir. Add citric acid (1.875 g) and stir until dissolved. Slowly neutralize the solution with concentrated ammonia until pH reaches 5. Add water to a total volume of 10 mL and homogenize.
[0051] The 40 to 80 mesh fractions were impregnated with Ga and La dopants by slowly adding the stock solution to the reticulated base catalyst in the vortex mixer solution (about 0.44 mL per gram of base catalyst support). The impregnated reticulated fraction was dried at 85°C overnight. The dried self-bound hybrid catalyst was then heated to 600°C at 2°C / min in a static muffle furnace and maintained at this temperature for 4 hours. After calcination, the self-bound hybrid catalyst was sieved into 40 to 80 mesh for testing.
[0052] Comparative Example 1
[0053] A metal oxide catalyst component containing gallium on a zirconia support was prepared by incipient wetness impregnation. Impregnation solutions of Ga(NO3)3×H2O and La(NO3)3×6H2O were prepared at concentrations of 0.57 mol / L and 0.17 mol / L, respectively, in deionized water. 10 grams of a ZrO2 support (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd., trade name RC-100, >94% monoclinic phase measured by XRD, pore volume = 0.7 mL / g measured by deionized water) were weighed and placed in a glass vial. Subsequently, 7 mL of the Ga / La impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the catalyst was dried overnight in an oven at 85°C, then heated to 550°C at 3°C / min and maintained at this temperature for 4 hours. After calcination, the catalyst was sieved to <200 mesh (75 μm) to remove larger agglomerated particles.
[0054] The mixed catalyst was prepared by mixing 8 grams of the above metal oxide catalyst components with 1.808 grams of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 10 minutes. Separately, pseudo-boehmite (AlOOH) (manufactured by Sasol Co., Ltd., trade name Catapal D) was peptized in water with a [HNO3] / [Al] ratio of 0.05 and a total solid content of 35% by weight using HNO3 (65% by weight H2O solution). The peptized pseudo-boehmite mixture was added to the dry mixed powder, with the goal of a pseudo-boehmite concentration of 24.6% by weight based on total solids. The paste was then mixed using a mortar and pestle for at least 10 minutes until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated to a temperature of 600°C at 2°C / min in a static muffle furnace and maintained at this temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 mesh to 80 mesh for testing.
[0055] Comparative Example 2
[0056] A metal oxide catalyst component containing gallium on a zirconium oxide support was prepared by incipient wetness impregnation. Impregnation solutions of Ga(NO3)3×H2O and La(NO3)3×6H2O were prepared at concentrations of 1 mol / L and 0.3 mol / L, respectively, in deionized water. 10 grams of a ZrO2 support (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd., trade name Z3186, >94% monoclinic phase measured by XRD, pore volume = 0.55 mL / g measured by deionized water) were weighed and placed in a glass vial. Afterwards, 5.5 mL of the Ga / La impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the catalyst was dried overnight in an oven at 85°C, then heated to 550°C at 3°C / min and maintained at this temperature for 4 hours. After calcination, the catalyst was sieved to <200 mesh (75 μm) to remove larger agglomerated particles.
[0057] The mixed catalyst was prepared by mixing 8 grams of the above metal oxide catalyst components with 1.808 grams of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 10 minutes. Separately, pseudo-boehmite (AlOOH) (manufactured by Sasol Co., Ltd., trade name Catapal D) was peptized in water with a [HNO3] / [Al] ratio of 0.05 and a total solid content of 35% by weight using HNO3 (65% by weight H2O solution). The peptized pseudo-boehmite mixture was added to the dry mixed powder, with the goal of a pseudo-boehmite concentration of 24.6% by weight based on total solids. The paste was then mixed using a mortar and pestle for at least 10 minutes until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated to a temperature of 600°C at 2°C / min in a static muffle furnace and maintained at this temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 mesh to 80 mesh for testing.
[0058] Comparative Example 3
[0059] The mixed base catalyst support was prepared by mixing 4 grams of zirconium oxide (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name RC-100) with 1 gram of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 2 minutes. A 20 wt% zirconium carbonate ammonium binder solution (manufactured by Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Zircosol ZA-20, pH≈10) was added to the dry mixed powder to give a final ZrO2 binder concentration of 20 wt% based on total solids. The paste was then mixed using a mortar and pestle for at least 15 minutes until an extrudable paste was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated to a temperature of 600°C at 2°C / min in a static muffle furnace and maintained at this temperature for 4 hours.
[0060] It is noted that alkaline ammonium zirconium carbonate solutions (pH≈10) damage the structural integrity of SAPO-34, which is detrimental to the productivity of the catalyst. The expected micropore volume of the hybrid catalyst is reduced to ≈80% compared to >95% for inventive Examples 1 and 2 (where the pH is about 5 to 6). Therefore, the pH of the zirconium oxide binder solution is critical to reduce damage to SAPO-34. Therefore, we did not conduct reactor testing of Comparative Example 3 in a reactor.
[0061] Catalytic performance data
[0062] The mixed catalyst was tested in a stainless steel fixed bed reactor system (7.7 mm inner diameter) under the following conditions: 420°C, H2 / CO=3, pressure=40 bar, weight hourly space velocity (WHSV)=1.54 hr -1 .
[0063] Before contacting with the synthesis gas, the self-binding catalyst was heated to the reaction temperature and pressure under nitrogen (N2). The reactor effluent composition was obtained by gas chromatography, and the conversion and carbon-based selectivity were calculated using the following equations:
[0064] X CO (%) = [(η CO, in – η CO, out ) / η CO, in ] · 100; and (1)
[0065] S j (%) = [α j · η j, out / (η CO, in – η CO, out )] · 100. (2)
[0066] Where X CO Defined as CO conversion (%), η CO,in is defined as the molar inlet flow rate of CO (μmol / s), η CO,out is the molar outlet flow rate of CO (μmol / s), S j is defined as the carbonyl selectivity (%) for product j, α j is the number of carbon atoms in product j, and n j,out is the molar outlet flow rate of product j (μmol / s).
[0067] The results of the catalytic tests are shown in Table 1 below. The reported conversion values (X CO ) is the average conversion level of the self-binding catalyst exposed to synthesis gas between 50 and 120 hours of on-stream time (TOS). The normalized deactivation rate k is calculated by fitting the data between 24 and 150 hours to a logarithmic decay: X / X0=a+k*ln(TOS(h)).
[0068] Table 1
[0069]
[0070] As can be observed in Table 1, the zirconia-bound bifunctional catalyst formulations exhibit lower deactivation rates (in absolute terms) than the corresponding alumina-bound systems. This behavior is observed for the different zirconia grades. For RC-100 grade zirconia, zirconia-bound Inventive Example 1 has a 23% lower deactivation rate than the alumina-bound Comparative Example 1. For Z3186 grade zirconia, zirconia-bound Inventive Example 2 has a 27% lower deactivation rate than the alumina-bound Comparative Example 2.
[0071] The present disclosure includes one or more non-limiting aspects. A first aspect includes a method for preparing a self-binding hybrid catalyst, the method comprising: mixing a powder mixture and a binder component to form a hybrid base catalyst; and adding an impregnation solution comprising gallium to the hybrid base catalyst to form the self-binding hybrid catalyst after drying and calcining, wherein the powder mixture comprises a metal oxide catalyst support and an 8-membered ring (8-MR) microporous catalyst component, the metal oxide catalyst support comprises zirconium oxide, and the binder component comprises a zirconium salt solution, a zirconium salt gel, a zirconium salt slurry, a slurry of a carbonate or oxide or hydroxide of zirconium, or a colloidal solution of a carbonate or oxide or hydroxide of zirconium, wherein the binder component has a pH of 2 to 8.
[0072] A second aspect includes any of the above aspects, wherein the gallium is introduced into the impregnation solution via a gallium-containing precursor.
[0073] A third aspect includes any of the above aspects, wherein the impregnation solution comprises at least one rare earth element.
[0074] A fourth aspect includes any of the above aspects, wherein the impregnation solution comprises one or more of nickel, palladium, or platinum.
[0075] A fifth aspect includes any of the above aspects, wherein the impregnation solution has a pH of 2 to 10.
[0076] A sixth aspect includes any of the above aspects, wherein the impregnation solution has a pH of 4 to 7.
[0077] A seventh aspect includes any of the above aspects, wherein the impregnation solution comprises a chelating agent or a complexing agent.
[0078] An eighth aspect includes any of the above aspects, wherein the chelating or complexing agent is selected from the group consisting of carboxylic acids, imino acids, amines, diols, and mixtures thereof.
[0079] A ninth aspect includes any of the above aspects, wherein the impregnation solution comprises citric acid.
[0080] A tenth aspect includes any of the above aspects, wherein the binder component comprises at least one of ammonium zirconium carbonate, zirconyl acetate, and zirconium hydroxide.
[0081] An eleventh aspect includes any of the above aspects, wherein the self-binding mixed catalyst has a particle size of 0.5 mm to 6.0 mm.
[0082] A twelfth aspect includes any of the above aspects, wherein the self-binding mixed catalyst has a particle size of less than 3.0 mm.
[0083] A thirteenth aspect includes any of the above aspects, wherein the microporous catalyst component comprises SAPO-34.
[0084] A fourteenth aspect includes any of the above aspects, wherein the microporous catalyst component comprises uncalcined SAPO-34.
[0085] A fifteenth aspect includes a method for preparing C2 to C4 hydrocarbons, the method comprising: introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a self-binding mixed catalyst formed according to the method of any one of the above aspects.
[0086] The subject matter of the present disclosure has been described in detail and by reference to specific embodiments. It should be understood that any detailed description of a component or feature of an embodiment does not necessarily imply that the component or feature is essential to the specific embodiment or any other embodiment. Further, it will be apparent to those skilled in the art that various modifications and changes may be made to the described embodiments without departing from the spirit and scope of the claimed subject matter.
[0087] It should be noted that one or more of the appended claims utilize the term "wherein" as a transitional expression. For purposes of defining the present technology, it should be noted that this term is introduced in the claims as an open transitional phrase that is used to introduce a recitation of a series of features of a structure and should be interpreted in a manner similar to the more commonly used open-ended term "comprising."
[0088] It should be understood that where a first component is described as "comprising" a second component, it is contemplated that in embodiments, the first component "consists of" or "consists essentially of" the second component. It should also be understood that where a first component is described as "comprising" a second component, it is contemplated that in embodiments, the first component may comprise at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, or even at least 99% of the second component (wherein % may be wt % or mole %).
[0089] For purposes of describing and defining the present technology, it should be noted that references herein to a variable that is a "function" of a parameter or another variable are not intended to indicate that the variable is exclusively a function of the listed parameter or variable. Rather, references herein to a variable that is a "function" of the listed parameters are intended to be open-ended such that the variable may be a function of a single parameter or multiple parameters.
[0090] It should also be noted that reference herein to "at least one" component, element, etc. should not be used to create an inference that alternative use of the article "a / an" should be limited to a single component, element, etc.
[0091] For purposes of describing and defining the present technology, it is noted that the terms "substantially" and "approximately" are used herein to represent the inherent degree of uncertainty that may be attributed to any quantitative comparison, value, measurement, or other representation. The terms "substantially" and "approximately" are also used herein to represent the degree by which a quantitative representation may vary from a stated reference without resulting in a change in the basic function of the subject matter at issue.
Claims
1. A method for preparing a self-binding mixed catalyst, the method comprising: mixing the powder mixture and the binder component to form a mixed base catalyst; as well as An impregnation solution comprising gallium is added to the hybrid base catalyst to form the self-binding hybrid catalyst after drying and calcination, wherein The powder mixture comprises a metal oxide catalyst support and an 8-membered ring (8-MR) microporous catalyst component, wherein the metal oxide catalyst support comprises zirconium oxide, and the binder component comprises a zirconium salt solution, a zirconium salt gel, a zirconium salt slurry, a slurry of a zirconium carbonate or oxide or hydroxide, or a colloidal solution of a zirconium carbonate or oxide or hydroxide, wherein the binder component has a pH of 2 to 8.
2. The method of claim 1, wherein the gallium is introduced into the impregnation solution via a gallium-containing precursor.
3. The method according to any one of claims 1 to 2, wherein the impregnation solution comprises at least one rare earth element.
4. The method of any one of claims 1 to 3, wherein the impregnation solution comprises one or more of nickel, palladium or platinum.
5. The method according to any one of claims 1 to 4, wherein the impregnation solution has a pH of 2 to 10.
6. The method according to any one of claims 1 to 5, wherein the impregnation solution has a pH of 4 to 7.
7. The method according to any one of claims 1 to 6, wherein the impregnation solution comprises a chelating or complexing agent.
8. The method of claim 7, wherein the chelating or complexing agent is selected from the group consisting of carboxylic acids, imino acids, amines, diols, and mixtures thereof.
9. The method according to any one of claims 1 to 8, wherein the impregnation solution comprises citric acid.
10. The method according to any one of claims 1 to 9, wherein the binder component comprises at least one of ammonium zirconium carbonate, zirconyl acetate, zirconium oxide and zirconium hydroxide.
11. The process according to any one of claims 1 to 10, wherein the self-binding mixed catalyst has a particle size of 0.5 mm to 6.0 mm.
12. The process according to any one of claims 1 to 11, wherein the self-binding mixed catalyst has a particle size of less than 3.0 mm.
13. The method of any one of claims 1 to 12, wherein the microporous catalyst component comprises SAPO-34.
14. The method of any one of claims 1 to 13, wherein the microporous catalyst component comprises uncalcined SAPO-34.
15. A method for preparing C2 to C4 hydrocarbons, the method comprising: introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; as well as The feed stream is converted into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a self-binding mixed catalyst formed according to the process of any one of claims 1 to 14.